الرقمنة على مستوى البلدية - لمادي، تبر; منصر، عيسى; مريتل، عبد المالك (جامعة الوادي University of El Oued, 2024)
يعتبر أسلوب الرقمنة الذي تتبناه الإدارة المحلية في الجزائر نقطة انطلاق جوهرية تساهم بشكل كبير في التحسين المستمر لنوعية الخدمات التي تقدمها الإدارة المحلية عموما و البلدية على وجه الخصوص، لكن ذلك يتوقف على العديد من الإمكانيات من أجل تقديم الخدمة المتميزة للمواطن المحلي، وتحقيق مستوى آداء مناسب لأجهزتها الإدارية، كالبنية التحتية الإلكترونية وتوافر جميع عناصر ومتطلبات تطبيق الإدارة الإلكترونية التي تشمل المعلوماتية الإتصالية والخدماتية وجميع المتطلبات البشرية، الإدارية والتقنية، كما لا يجب إهمال ضرورة وجود إرادة سياسية قوية تتولى مسؤولية التغيير في هذا المجال، فعلى الرغم من تواصل جهود الدولة الجزائرية في مجال إرساء وتجسيد متطلبات الإدارة الإلكترونية في البلديات إلا أن هذا التحول مازال في مراحله الأولى لأن هناك عدة تحديات لابد من تجاوزها و إجاد الحلول المناسبة لها من أجل تجسيد مشروع الإدارة الإلكترونية في البلدية، وكل ذلك يحتاج الى وضع رؤية استراتيجية شاملة بمشاركة الدولة وجميع الفاعلين بما يضمن الانتقال الإيجابي من الإدارة التقليدية الى الإدارة الإلكترونية ومن تم تحسين وترقية الخدمات التي تقدمها الإدارة المحلية للمواطنين والرفع من مستوى التنمية الاقتصادية والاجتماعية. ولقد خطت الإدارة المحلية الجزائرية خاصة البلدية اليوم خطوات جبارة في طريق اللحاق بركب الإدارة الإلكترونية لتصير أكثر تكيفا مع التطور العلمي والتكنولوجي، ومع متطلبات النظام الاقتصادي والاجتماعي، وحتى السياسي والمستقبلي للجزائر، وبدأت تظهر أولى البوادر فيه من خلال رقمنة سجلات الحالة المدنية وبيومترية جواز السفر وبطاقة التعريف موضوع الدراسة، ومن أبرز أهداف هذه الاستراتيجية الرقمية هو ربح الوقت والجهد والتكلفة ومواكبة المتطلبات المجتمعية، وتخليص الإدارة من البيروقراطية والفساد وتجديد ثقة المواطن فيها، ولم تدخر الحكومة الجزائرية والسلطات العليا في تسخير كل الوسائل التشريعية والمادية والبشرية لإنجاح هذه الاستراتيجية، إلا أن التحدي لا يزال صعبا لوجود العديد من العراقيل؛ كالمشاكل المرتبطة بشبكات الأنترنت وشبكات الألياف البصرية، إضافة إلى الصعوبات المرتبطة بالمؤهلات البشرية والإمكانيات المادية في معظم البلديات. The method of digitization adopted by the local administration in Algeria is considered an essential starting point that contributes significantly to the continuous improvement of the quality of services provided by the local administration in general and the municipality in particular, but this depends on many possibilities in order to provide distinguished service to the local citizen, and achieve an appropriate level of performance. For its administrative bodies, such as the electronic infrastructure and the availability of all elements and requirements for implementing electronic administration, which includes communication and service information and all human, administrative and technical requirements. The need for a strong political will to assume responsibility for change in this field must not be neglected, despite the continuing efforts of the Algerian state in the field of Establishing and embodying the requirements of electronic management in municipalities. However, this transformation is still in its early stages because there are several challenges that must be overcome and appropriate solutions found in order to materialize the electronic management project in the municipality. All of this requires developing a comprehensive strategic vision with the participation of the state and all actors in a way that ensures the positive transition from traditional administration to electronic administration has improved and upgraded the services provided by the local administration to citizens and raised the level of economic and social development. Today, the Algerian local administration has taken tremendous steps towards catching up with electronic administration to become more adaptable to scientific and technological development, and to the requirements of the economic and social system, and even the political and future of Algeria. The first signs of it have begun to appear through the digitization of civil status records and the biometrics of the passport and identification card subject to the issue. Study: One of the most prominent goals of this digital strategy is to save time, effort, and cost, keep up with societal requirements, rid the administration of bureaucracy and corruption, and renew citizen confidence in it. The Algerian government and higher authorities have spared no effort in harnessing all legislative, material, and human means to make this strategy a success, but the challenge is still difficult. Because there are many obstacles; Such as problems associated with the Internet and fiber optic networks, in addition to the difficulties associated with human qualifications and financial capabilities in most municipalities.
ماستر اداري